Membrane electrode with gradient differentiation, preparation method and application

By using gradient differential spraying technology and a combination of platinum carbon catalyst and iridium dioxide catalyst on the anode side of the membrane electrode, a membrane electrode with gradient differential catalyst distribution is formed, and the existing membrane electrodes are solved in the ammonia hydrogen fuel cell system. Extreme phenomena and life span problems achieve higher stability and adaptability.

CN119481090APending Publication Date: 2025-02-18FUZHOU UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411398275.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing membrane electrodes are prone to reverse the polarity phenomenon in hydrogen and nitrogen environments, which affects the life of the membrane electrodes and is not suitable for ammonia hydrogen fuel cell systems that produce hydrogen and nitrogen as fuels due to ammonia decomposition.

Method used

Using the gradient differentiated membrane electrode preparation method, a catalytic layer is formed on the anode side of the proton exchange membrane through ultrasonic spraying technology. The thickness of the catalytic layer gradually increases along the length direction of the proton exchange membrane, combining platinum carbon catalyst and iridium dioxide catalyst. The use of the film electrodes are formed with gradient differentiated catalyst distribution.

Benefits of technology

The diffusion resistance of the hydrogen and nitrogen mixture in the catalytic layer channel in the rear end of the flow field is improved, the anti-reverse ability and long-term stability of the membrane electrode are improved, and the long-term and stable operation of the fuel cell is adapted to the hydrogen and nitrogen mixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481090A_ABST
    Figure CN119481090A_ABST
Patent Text Reader

Abstract

The invention discloses a gradient differentiated membrane electrode, a preparation method and application. The preparation method comprises the following steps: firstly, mixing a platinum-carbon catalyst, deionized water and an iridium dioxide catalyst to obtain a dispersion solvent; mixing with deionized water and a perfluorosulfonic acid ionomer solution, carrying out ultrasonic cleaning in an ice-water bath for 20-35 minutes, and then adding isopropanol or ethanol; adding a platinum-carbon catalyst or an iridium dioxide catalyst and carrying out ultrasonic cleaning; respectively spraying the colloidal solution on the anode side and the cathode side of a proton exchange membrane, wherein the thickness of a catalyst layer on the anode side of the proton exchange membrane is gradually increased along the length direction of the proton exchange membrane; and finally, carrying out hot-pressing plastic packaging treatment on the sprayed proton exchange membrane, and after plastic packaging treatment, placing the gas diffusion electrodes on the cathode side and the anode side of the proton exchange membrane and carrying out hot-pressing treatment. The gradient differentiated membrane electrode is obtained. According to the gradient differentiated membrane electrode, the anti-pole-reversal capability of the hydrogen side is improved, and the long-term stable operation of the fuel cell under the hydrogen-nitrogen mixed gas can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cell membrane electrode technology, and in particular to a gradient-differentiated membrane electrode suitable for an ammonia-hydrogen fuel cell, a preparation method and an application thereof. Background Art

[0002] Ammonia, as a chemical hydrogen storage medium, has the advantages of high energy density, easy storage and transportation. Ammonia is cracked into nitrogen, hydrogen and trace ammonia under moderate temperature and catalyst, and the residual trace ammonia is removed by adsorption. Then the hydrogen-nitrogen mixture is introduced into the fuel cell for electrochemical reaction and power generation. This can overcome the defects of high storage and transportation costs, weak intrinsic safety and flammable and explosive hydrogen under high-pressure hydrogen storage. When the hydrogen-nitrogen mixture enters the fuel cell, under high current and high back pressure, the hydrogen concentration decreases along the flow field direction. In addition, 25% nitrogen dilutes the hydrogen concentration and hinders the diffusion channel of hydrogen. This can easily cause the electrode reaction to not proceed normally, causing reverse polarity, which leads to carbon corrosion and a sharp decrease in the life of the membrane electrode.

[0003] Chinese patent CN115133043A discloses a membrane electrode containing a gradient cathode catalyst layer, a preparation method and an application thereof; the membrane electrode comprises a cathode catalyst layer, a proton exchange membrane and a gas diffusion layer, the cathode catalyst layer comprises a first catalyst layer, a second catalyst layer and a third catalyst layer; the proton exchange membrane is connected to the first catalyst layer, the first catalyst layer is connected to the second catalyst layer and the third catalyst layer in sequence, and the third catalyst layer is connected to the gas diffusion layer; the raw materials of the cathode catalyst layer include a platinum-containing catalyst and a perfluorosulfonic acid ionomer; wherein the cathode catalyst layer exists in a gradient form, and the gradient design is used to increase the gap in the catalyst layer from the proton exchange membrane to the gas diffusion layer, thereby improving water vapor transmission and the rated power and performance of the fuel cell; however, the membrane electrode is prone to reverse order phenomenon in hydrogen and nitrogen environments, which affects the life of the membrane electrode.

[0004] Chinese patent CN1183380597A discloses a composite membrane layer and a preparation method thereof, a membrane electrode, and a fuel cell. The composite membrane layer includes a proton exchange membrane, a first catalytic layer arranged on one side of the proton exchange membrane, the first catalytic layer includes a water electrolysis catalyst, a dispersant, a platinum-carbon catalyst, and an ion polymer, and a second catalytic layer arranged on the first catalytic layer, the second catalytic layer includes a platinum-carbon catalyst, a dispersant, and an ion polymer. The composite membrane layer increases the active sites of the water electrolysis catalyst and inhibits the carbon corrosion reaction under high voltage potential by adjusting the carbon carrier mass ratio of the ion polymer and the platinum-carbon catalyst in the first and second catalytic layers; however, the composite membrane layer has pore diffusion resistance in hydrogen and nitrogen environments by adjusting the pore size distribution of the catalytic layer, which affects the long-term stability of the membrane electrode. Summary of the invention

[0005] In view of the problem that the membrane electrode in the prior art usually has uniform thickness and is not suitable for an ammonia-hydrogen fuel cell system that generates hydrogen and nitrogen as fuel by decomposing ammonia; a gradient-differentiated membrane electrode, a preparation method and an application are provided, which can improve the diffusion resistance of the hydrogen-nitrogen mixed gas in the catalytic layer pores in the rear end of the flow field, improve the membrane electrode's anti-reverse polarity ability and enhance the long-term stable performance of the membrane electrode.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a gradient-differentiated membrane electrode preparation method, comprising the following steps: step 1: mixing a platinum-carbon catalyst with deionized water and an iridium dioxide catalyst to obtain a dispersed solvent; step 2: mixing the dispersed solvent with deionized water and a perfluorosulfonic acid ionomer solution to obtain a mixed solution, placing the obtained mixed solution in an ice water bath for ultrasonic cleaning for 20 to 35 minutes, and then adding ethanol or isopropanol to the mixed solution; step 3: adding a platinum-carbon catalyst or an iridium dioxide catalyst to the mixed solution after ultrasonic cleaning, and then ultrasonic cleaning the mixed solution in an ice water bath again. Acoustic cleaning; dispersing the platinum carbon and iridium dioxide catalyst particles in the dispersing solvent to form a colloidal solution; step four: placing the proton exchange membrane on an ultrasonic spraying device for heating, spraying the colloidal solution containing the platinum carbon catalyst and the iridium dioxide catalyst on the anode side and the cathode side of the proton exchange membrane respectively, and the thickness of the catalytic layer on the anode side of the proton exchange membrane gradually increases along the length direction of the proton exchange membrane; step five: hot pressing and sealing the sprayed proton exchange membrane, placing the gas diffusion electrode on the cathode side and the anode side of the proton exchange membrane after the sealing treatment, and finally hot pressing; a gradient-differentiated membrane electrode is obtained.

[0007] Furthermore, in step one, the dispersion solvent containing the platinum-carbon catalyst and the iridium dioxide catalyst also includes an organic solvent, and the organic solvent is any one or more of ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol or n-butanol.

[0008] Furthermore, in step three, the mixed solution after another ultrasonic cleaning is placed in an ultrasonic environment for ultrasonic crushing; a colloidal solution is formed; the mass ratio of the platinum carbon catalyst, the iridium dioxide catalyst, the deionized water and the perfluorosulfonic acid ionomer solution in the dispersed solvent is (0.08-1.25): (0.02-0.15): (40-70): (15-30); during the ultrasonic crushing process, the frequency of the ultrasonic crushing is 10-44KHz, and the ultrasonic crushing time is 1-5h; the temperature range of the ice water bath is -8-3°C.

[0009] Furthermore, in step 4, before heating the proton exchange membrane, the proton exchange membrane is cut into a quadrilateral structure and immersed in deionized water, and the immersed proton exchange membrane is taken out from the deionized water and immersed in an acid solution, wherein the acid solution is sulfuric acid, phosphoric acid, hydrochloric acid or an organic acid, and the concentration range of the acid solution is 0.5 to 1.5 L / mol.

[0010] Furthermore, the colloidal solution containing the platinum carbon catalyst and the iridium dioxide catalyst is sprayed on the anode side and the cathode side of the proton exchange membrane respectively by ultrasonic spraying, doctor blade coating, slit coating or screen printing.

[0011] A gradient-differentiated membrane electrode prepared by a gradient-differentiated membrane electrode preparation method comprises an anode catalyst layer, a cathode catalyst layer, a proton exchange membrane, a cathode gas diffusion layer and an anode gas diffusion layer; the anode catalyst layer and the cathode catalyst layer are respectively covered on both sides of the proton exchange membrane, the cathode gas diffusion layer is covered on the anode catalyst layer, and the anode gas diffusion layer is covered on the cathode catalyst layer, the thickness of the anode catalyst layer gradually increases along the length direction of the proton exchange membrane, and both the anode catalyst layer and the cathode catalyst layer contain platinum metal, iridium metal elements and perfluorosulfonic acid ionomer.

[0012] Furthermore, the anode catalyst layer and the cathode catalyst layer both include a platinum-carbon catalyst and a platinum alloy catalyst, the alloying elements in the platinum alloy catalyst are one or more of Co, Ni, Ru, Cu, and Fe; the mass fraction of platinum in the platinum-carbon catalyst is 10 to 80%; the mass fraction of iridium metal elements in the anode catalyst layer and the cathode catalyst layer are both 50 to 90%; the mass fraction of perfluorosulfonic acid ionomer in the anode catalyst layer is 20 to 35%.

[0013] Furthermore, the amount of platinum metal carrier on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane; the amount of iridium loaded on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane, the pore diameter on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane, and the thickness of the anode catalyst layer increases linearly along the length direction of the proton exchange membrane; the thickness range of the anode catalyst layer is 5 to 15 um.

[0014] The invention discloses an application of a gradient-differentiated membrane electrode in the field of fuel cells.

[0015] The present invention discloses a method for preparing a gradient-differentiated membrane electrode, which utilizes CCM technology and gradient-differentiated spraying to form a precious metal load corresponding to the low load in the initial section of the flow field, and a high load and high porosity catalyst layer corresponding to the catalyst layer at the end of the flow field on the anode side of the proton exchange membrane. Thus, a gradient-differentiated catalyst distribution is formed in the catalyst layer, corresponding to the initial end, middle end and end of the flow field, which can prevent the reverse polarity phenomenon caused by the low hydrogen concentration at the end of the flow field. At the same time, the high porosity layer accelerates the diffusion of hydrogen, and nitrogen is also conducive to the removal of liquid water. In addition, the membrane electrode with a gradient-differentiated anode catalyst layer in the membrane electrode provided in the present invention is adapted to a hydrogen-nitrogen mixture, which can improve the long-term stable operation of the fuel cell under a hydrogen-nitrogen mixture. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a schematic structural diagram of the anode catalyst layer, proton exchange membrane and cathode catalyst layer of the gradient differentiated membrane electrode described in the present invention. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The present invention provides a method for preparing a gradient-differentiated membrane electrode, comprising the following steps:

[0020] Step 1: mixing a platinum-carbon catalyst, an iridium dioxide catalyst and deionized water to obtain a dispersion solvent;

[0021] Step 2: Mix the dispersion solvent with deionized water and the perfluorosulfonic acid ionomer solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 20 to 35 minutes, and then add ethanol or isopropanol to the mixed solution;

[0022] Step 3: Adding the platinum-carbon catalyst or the iridium dioxide catalyst again to the mixed solution after ultrasonic cleaning, and then continuing the ultrasonic cleaning in an ice-water bath environment; so that the platinum-carbon and iridium dioxide catalyst particles are dispersed in the dispersing solvent to form a colloidal solution;

[0023] Step 4: placing the proton exchange membrane on an ultrasonic spraying device for heating, spraying a colloidal solution containing a platinum-carbon catalyst and an iridium dioxide catalyst on the anode side and the cathode side of the proton exchange membrane respectively, wherein the thickness of the catalyst layer on the anode side of the proton exchange membrane gradually increases along the length direction of the proton exchange membrane;

[0024] Step 5: The sprayed proton exchange membrane is heat-pressed and sealed with a PET film frame. After the sealing, the gas diffusion electrodes are placed on the cathode side and the anode side of the proton exchange membrane, and finally hot-pressed to obtain a gradient-differentiated membrane electrode.

[0025] In step 1, the platinum-carbon catalyst and iridium dioxide are selected to promote the release of electrons and the generation of protons by hydrogen during the operation of the fuel cell, reduce the activation energy required for the reaction, and improve the reaction rate and operation efficiency in the fuel cell; at the same time, the platinum-carbon catalyst has good chemical stability and thermal stability in the fuel cell environment, and can maintain catalytic activity for a long time; iridium dioxide can promote the transfer of electrons, reduce the reaction overpotential and improve the energy conversion efficiency, and promote the hydrogen evolution reaction, which can slow down or organize the occurrence of the reverse phenomenon; after the platinum-carbon catalyst and the iridium dioxide catalyst are mixed to form a dispersed solvent, deionized water is added to the mixed solvent for wetting, and the catalyst surface is removed. Impurities are removed, pollution to the catalyst is reduced and the surface of the catalyst is kept clean and active, so that the platinum-carbon catalyst and the iridium dioxide catalyst are better dispersed in the solvent, the contact efficiency between the catalyst and the reactant is improved, and a certain humidity of the catalyst is maintained to avoid catalyst deactivation in the mixed dispersion solvent containing the platinum-carbon catalyst and the iridium dioxide, thereby improving the catalytic effect; more specifically, the obtained dispersion solvent containing the platinum-carbon catalyst and the iridium dioxide catalyst also includes an organic solvent, such as any one or more of ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol or n-butanol, thereby better improving the catalytic effect of the catalyst, improving the stability of the catalyst and extending its service life.

[0026] In step 2, the dispersion solvent containing the platinum-carbon catalyst and the iridium dioxide catalyst obtained in step 1 is mixed with deionized water, a perfluorosulfonic acid ionomer solution, isopropanol or ethanol to obtain a mixed solution, and the obtained mixed solution is placed in an ice-water bath for ultrasonic cleaning; wherein, the dispersion solvent is first mixed with deionized water and a perfluorosulfonic acid ionomer solution and isopropanol with a stabilizing function to remove residual pollutants and impurities in the mixed solution, and the perfluorosulfonic acid ionomer solution can enhance the interaction between the catalyst particles and the carrier, improve the stability of the catalyst, and can also serve as a carrier of the catalyst; by adding isopropanol or ethanol, the dispersion of the catalyst particles can be promoted, which is beneficial to the subsequent redox reaction and improves the reaction efficiency; specifically, the solute of the perfluorosulfonic acid ionomer solution is a perfluorosulfonic acid ionomer, and the perfluorosulfonic acid ionomer is a perfluorosulfonic acid membrane (Nafion) or a perfluorosulfonic acid type proton exchange membrane. Replace the membrane (Flemion); secondly, the mixed solution is ultrasonically cleaned in an ice-water bath. Ultrasonic cleaning can produce strong cavitation effects and microjets, which can penetrate into the tiny gaps of the catalyst particles and peel off the impurities and pollutants attached to the surface of the particles, thereby further purifying the catalyst; at the same time, the low temperature environment of the ice-water bath helps to slow down the chemical reaction rate of the catalyst particles and make the bond between the catalyst particles and the carrier more firm, reducing the decrease in bonding force or shedding caused by high temperature; during the ultrasonic cleaning process, the catalyst particles are fully in contact with the perfluorosulfonic acid ionomer solution, which helps the catalyst particles to better adhere to the carrier and form a stable catalyst layer; through ultrasonic cleaning and ice-water bath treatment, the dispersion and stability of the catalyst particles are improved, and the contact area between the catalyst and the reactants is increased, thereby improving the reaction activity of the catalyst; better control the reaction path and reduce the generation of by-products.

[0027] In step three, after completing the preliminary ultrasonic cleaning of the mixed solution consisting of the dispersion solvent, deionized water and perfluorosulfonic acid ionomer solution in an ice water bath environment; adding the platinum carbon catalyst or the iridium dioxide catalyst again, and continuing the ultrasonic cleaning in the ice water bath environment, compared with the situation of mixing the catalyst with deionized water and perfluorosulfonic acid ionomer at one time, the catalyst and the perfluorosulfonic acid ionomer can be evenly mixed, and the reaction activity of the catalyst is better improved; after completing the uniform mixing of the dispersion solvent and the perfluorosulfonic acid ionomer solution, the evenly mixed solution is placed in an ultrasonic environment for ultrasonic crushing, so that the platinum carbon catalyst and the iridium dioxide catalyst particles are dispersed in the dispersion solvent to form a colloidal solution containing the platinum carbon catalyst and the iridium dioxide catalyst; the colloidal solution can be used as a carrier of the catalyst to make the platinum carbon catalyst and the iridium dioxide catalyst evenly distributed, maximize the contact area between the catalyst and the reactant, thereby improving the reaction efficiency and fuel cell efficiency. The cell performance is also beneficial to prolonging the service life and stability of the fuel cell; more specifically, the mass ratio of the platinum carbon catalyst, the iridium dioxide catalyst, the deionized water and the perfluorosulfonic acid ionomer solution in the dispersed solvent is (0.08-1.25): (0.02-0.15): (40-70): (15-30); for example, 0.08:0.02:40:15, 1:0.1:70:30, 1:0.05:50:20 or 1.25:0 .15:65:25; during the ultrasonic crushing process, the frequency of ultrasound is 10-44KHz, for example, 10KHz, 20KHz, 30KHz, 40KHz or 44KHz; the ultrasonic crushing time is 1-5h, for example, 1h, 2h, 3h, 4h or 5h, etc.; the temperature range of the ice water bath is -8-3°C, for example, -8°C, -7°C, -6°C, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C or 3°C.

[0028] In step 4, in order to improve the conductivity of the proton exchange membrane and improve the power generation efficiency of the subsequent fuel cell; preferably, before heating the proton exchange membrane, the proton exchange membrane is cut into a quadrilateral structure and soaked in deionized water, and then the soaked proton exchange membrane is soaked in an acid solution, and the membrane is treated with the acid solution to increase the conductivity of the membrane, because the acid can increase the proton concentration in the membrane, thereby increasing the electron flow, which is beneficial to the improvement of conductivity; the proton exchange membrane after acid treatment is placed in a blast drying oven for drying and standby; wherein the acid solution used includes various acid solutions, such as sulfuric acid, phosphoric acid, hydrochloric acid or organic acid, and the concentration range of the acid solution is 0.5 to 1.5 L / mol, such as 0.5 L / mol, 0.6 L / mol, 0.7 L / mol, 0.8 L / mol, 1 L / mol or 1.5 L / mol, etc.;

[0029] After drying, the proton exchange membrane after the above treatment is placed on the vacuum adsorption heating plate of the ultrasonic spraying equipment, the temperature of the hot plate is maintained, the angle of the membrane is adjusted, and the membrane is ensured to cover the small holes of the vacuum adsorption and is located at the center of the spraying. The other areas of the vacuum adsorption plate are covered with a polyimide membrane to ensure that the proton exchange membrane is firmly adsorbed on the heating plate and the effective active area of ​​the membrane electrode is determined; the platinum carbon catalyst and the iridium dioxide catalyst colloidal solution obtained in step 2 are coated on the anode side of the proton exchange membrane. During the spraying process, the gradient parameterization of the anode catalyst layer is achieved by changing the process parameters, such as the spraying flow rate and the moving speed, so that the thickness of the catalyst layer on the anode side of the proton exchange membrane gradually increases along the length direction of the proton exchange membrane; more specifically, the temperature range of the hot plate is 60 to 70° C., such as 60° C., 65° C. or 70° C.; the thickness of the catalyst layer on the anode side of the proton exchange membrane gradually increases with the flow direction of the gas, such as hydrogen and nitrogen; better adapt to the hydrogen concentration drop during the flow of hydrogen in a hydrogen-nitrogen environment and the nitrogen dilution of the hydrogen concentration, which hinders the diffusion of hydrogen.

[0030] After spraying the anode side of the proton exchange membrane, turn the other side of the proton exchange membrane over, that is, set the cathode side of the proton exchange membrane upward, and place the proton exchange membrane on the vacuum adsorption heating plate of the ultrasonic spraying equipment. Maintain the temperature of the hot plate, adjust the angle of the membrane, ensure that the membrane covers the small holes of vacuum adsorption and is located at the center of the spraying, and cover other areas of the vacuum adsorption plate with a polyimide membrane to ensure that the proton exchange membrane is firmly adsorbed on the heating plate; determine the effective active area of ​​the membrane electrode and adjust the process parameters; evenly coat the platinum carbon and iridium dioxide iridium catalyst colloid solution on the cathode side of the proton exchange membrane; complete the spraying of the catalyst colloid solution on the cathode and anode sides of the proton exchange membrane.

[0031] More specifically, the process of coating the catalyst colloidal solution on the proton exchange membrane includes ultrasonic spraying, blade coating, slit coating and screen printing; preferably, the process is ultrasonic spraying.

[0032] In step five, the catalyst-coated proton exchange membrane obtained in step three is subjected to hot-pressing and plastic-sealing treatment with a PET film frame, and then the cathode gas diffusion layer electrode is placed on the cathode side of the catalyst-coated proton exchange membrane, and the anode gas diffusion layer electrode is placed on the anode side of the catalyst-coated proton exchange membrane, and then placed in a metal pressing plate and put into a hot press, and the hot plate temperature, pressure and holding time are set to obtain a gradient-differentiated anode catalyst layer membrane electrode.

[0033] By uniformly mixing perfluorosulfonic acid ionomer with platinum carbon catalyst and iridium dioxide catalyst, and combining ice water bath and ultrasonic cleaning for purification, a colloidal solution with uniform distribution of catalyst elements and large contact area is prepared, and gradient spraying is performed in combination with ultrasonic spraying and other processes. It not only better adapts to the reaction environment in which the hydrogen concentration in the hydrogen-nitrogen environment gradually decreases with the flow process, reduces the reverse polarity phenomenon, carbon corrosion and other defects caused by the decrease in hydrogen concentration in the hydrogen-nitrogen environment, and improves the service life and stability of the membrane electrode, but also better promotes the oxidation reaction of hydrogen and nitrogen in the flow process, so that hydrogen can undergo oxidation reaction evenly, reduces the influencing factors in the flow process, and improves the controllability of the fuel cell reaction process.

[0034] like Figure 1 As shown, the present application also discloses a gradient-differentiated membrane electrode prepared by the above-mentioned gradient-differentiated membrane electrode preparation method, comprising an anode catalyst layer 1, a cathode catalyst layer 3, a proton exchange membrane 2, a cathode gas diffusion layer and an anode gas diffusion layer (not shown); the anode catalyst layer 1 and the cathode catalyst layer 3 are respectively covered on both sides of the proton exchange membrane 2, the cathode gas diffusion layer is covered on the cathode catalyst layer 3, and the anode gas diffusion layer is covered on the anode catalyst layer 1;

[0035] The thickness of the anode catalyst layer 1 gradually increases along the length direction of the proton exchange membrane 2 . Both the anode catalyst layer 1 and the cathode catalyst layer 3 contain platinum metal, iridium metal element and perfluorosulfonic acid ionomer.

[0036] Among them, the anode catalyst layer 1 and the cathode catalyst layer 3 both include a platinum-carbon catalyst and a platinum alloy catalyst, the alloying elements in the platinum alloy catalyst are one or more of Co, Ni, Ru, Cu, and Fe; the mass fraction of platinum in the platinum-carbon catalyst is 10 to 80%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc., the anode catalyst The mass fraction of iridium in the cathode catalyst layer 1 and the cathode catalyst layer 3 is 50-90%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%; the perfluorosulfonic acid ionomer is a perfluorosulfonic acid membrane (Nafion) or a perfluorosulfonic acid proton exchange membrane (Flemion); the mass fraction of the perfluorosulfonic acid ionomer in the anode catalyst layer 1 is 20-35%, for example, 20%, 25%, 30% or 35%.

[0037] The amount of platinum metal carrier on the anode catalyst layer 1 gradually increases along the length direction of the proton exchange membrane 2 to correspond to the flow direction of the subsequent gas. Specifically, the amount of platinum metal carrier on the anode catalyst layer 1 gradually increases along the length direction of the proton exchange membrane 2; the amount of iridium carrier on the anode catalyst layer 1 gradually increases along the length direction of the proton exchange membrane 2, the pore diameter size on the anode catalyst layer 1 gradually increases along the length direction of the proton exchange membrane 2, and the thickness of the anode catalyst layer 1 increases linearly along the length direction of the proton exchange membrane 2; more preferably, the thickness range of the anode catalyst layer 1 is 5 to 15 μm. ; For example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm; by gradually increasing the thickness, platinum metal carrier amount, iridium metal carrier amount and pore diameter on the anode catalyst layer along the length direction of the proton exchange membrane, that is, the flow direction of the gas, so as to better adapt to the fuel cell environment with hydrogen and nitrogen as reaction gases, and prevent the reverse polarity phenomenon caused by the decrease in concentration of hydrogen and nitrogen during the flow process at the end of the gas flow field. At the same time, the high pore layer can accelerate the diffusion of hydrogen, which can improve the long-term stable operation of the fuel cell under the hydrogen and nitrogen mixture.

[0038] The following is a further description of the gradient-differentiated membrane electrode preparation method described in the present application in conjunction with the embodiments.

[0039] Example 1

[0040] Step 1: Pt on Vulacan XC-72 catalyst was placed in a bottle, and then IrO2 catalyst, 10 g of deionized water and a magnetic stirrer were added to obtain a dispersion solvent, and the dispersion solvent was stirred at a stirring speed of 600 rpm for 3 min;

[0041] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 10 minutes, and then add 25 g of isopropanol to the mixed solution;

[0042] Step 3: Add platinum-carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice-water bath environment; ultrasonically crush the slurry after ultrasonic cleaning for 3 consecutive times in an ice-water bath for 20 minutes; disperse the platinum-carbon and iridium dioxide catalyst particles in the dispersing solvent, and then magnetically stir at 300 rpm to form a colloidal solution;

[0043] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The blocks of different sizes were first soaked in deionized water, then treated in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, activating the proton conductivity of the Nafion membrane, and then placed in a blast drying oven at 60°C for 2 hours for standby use to obtain a pretreated proton exchange membrane; then ultrasonic spraying was used, with a nitrogen carrier gas pressure gauge of 50Pa, a slurry spraying flow rate of 1ml / min, a horizontal nozzle moving speed of 10mm / s, a vertical nozzle moving speed of 5mm / s, and a horizontal nozzle spraying speed in the vertical direction. Gradually increase, ultrasonically spray the Pt / XC-72 catalyst and IrO2 catalyst colloid solutions on the membrane on the anode side respectively, to achieve differentiated thickness gradient of the catalytic layer and linear increase in thickness, finally turn the proton exchange membrane over, the nitrogen carrier gas pressure gauge pressure is 50Pa, the slurry spraying flow rate is 1ml / min, the horizontal nozzle movement speed is 10mm / s and remains unchanged, the vertical nozzle movement speed is 5mm / s, and the Pt / XC-72 catalyst and IrO2 catalyst colloid solutions are ultrasonically sprayed on the membrane on the cathode side respectively, to achieve uniform coating of the catalytic layer on the cathode side.

[0044] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalyst layers of the prepared proton exchange membrane, respectively, use PEN film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 110°C, 5MPa pressure, and hot press for 2 minutes to obtain a gradient differentiated membrane electrode.

[0045] Example 2

[0046] Step 1: Pt on Vulacan XC-72 catalyst was placed in a bottle, and then IrO2 catalyst, 10 g of deionized water and a magnetic stirrer were added to obtain a dispersion solvent, and the dispersion solvent was stirred at a stirring speed of 600 rpm for 3 min;

[0047] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 10 minutes, and then add 10 g of ethanol to the mixed solution;

[0048] Step 3: Add platinum-carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice-water bath environment; ultrasonically crush the slurry after ultrasonic cleaning for 3 consecutive times in an ice-water bath for 20 minutes; disperse the platinum-carbon and iridium dioxide catalyst particles in the dispersing solvent, and then magnetically stir at 300 rpm to form a colloidal solution;

[0049] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The blocks were then treated in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, activating the proton conductivity of the Nafion membrane, and then placed in a blast drying oven at 60°C for 2 hours for standby use to obtain a pretreated proton exchange membrane; ultrasonic spraying was then used, with a nitrogen carrier gas pressure gauge of 50Pa, a slurry spraying flow rate of 1ml / min, a horizontal nozzle moving speed of 10mm / s, a vertical nozzle moving speed of 5mm / s, and the horizontal nozzle spraying speed gradually increased along the vertical direction. The Pt / XC-72 catalyst and IrO2 catalyst colloidal solutions were ultrasonically sprayed on the membrane on the anode side, respectively, to achieve differentiated thickness gradient of the catalytic layer and linear increase in thickness. Finally, the proton exchange membrane was turned over, the nitrogen carrier gas pressure gauge pressure was 50Pa, the slurry spraying flow rate was 1.3ml / min, the horizontal nozzle movement speed was 10mm / s and remained unchanged, the vertical nozzle movement speed was 8mm / s, and the Pt / XC-72 catalyst and IrO2 catalyst colloidal solutions were ultrasonically sprayed on the membrane on the cathode side, respectively, to achieve uniform coating of the catalytic layer on the cathode side.

[0050] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalytic layers of the prepared proton exchange membrane, respectively, use PI film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 140°C, 7MPa pressure, and hot press for 2 minutes to obtain a gradient differentiated membrane electrode.

[0051] Example 3

[0052] Step 1: Pt on Vulacan XC-72 catalyst was placed in a bottle, and then IrO2 catalyst, 10 g of deionized water and a magnetic stirrer were added to obtain a dispersion solvent, and the dispersion solvent was stirred at a stirring speed of 600 rpm for 3 min;

[0053] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 10 minutes, and then add 10 g of ethanol to the mixed solution;

[0054] Step 3: Add platinum carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice water bath environment; disperse through a nano-scale sand mill, the speed of the disperser is 2000rpm, and the dispersion time is 30min; disperse the platinum carbon and iridium dioxide catalyst particles in the dispersion solvent, collect the dispersed catalyst slurry for degassing treatment, and then magnetically stir at 300rpm to form a colloidal solution;

[0055] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The blocks were then treated in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, activating the proton conductivity of the Nafion membrane, and then placed in a blast drying oven at 60°C for 2 hours for standby use to obtain a pretreated proton exchange membrane; ultrasonic spraying was then used, with a nitrogen carrier gas pressure gauge of 50Pa, a slurry spraying flow rate of 1ml / min, a horizontal nozzle moving speed of 10mm / s, a vertical nozzle moving speed of 5mm / s, and the horizontal nozzle spraying speed gradually increased along the vertical direction. The Pt / XC-72 catalyst and IrO2 catalyst colloidal solutions were ultrasonically sprayed on the membrane on the anode side, respectively, to achieve differentiated thickness gradient of the catalytic layer and linear increase in thickness. Finally, the proton exchange membrane was turned over, the nitrogen carrier gas pressure gauge pressure was 50Pa, the slurry spraying flow rate was 1.3ml / min, the horizontal nozzle movement speed was 10mm / s and remained unchanged, the vertical nozzle movement speed was 8mm / s, and the Pt / XC-72 catalyst and IrO2 catalyst colloidal solutions were ultrasonically sprayed on the membrane on the cathode side, respectively, to achieve uniform coating of the catalytic layer on the cathode side.

[0056] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalytic layers of the prepared proton exchange membrane, respectively, use PI film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 140°C, 7MPa pressure, and hot press for 2 minutes to obtain a gradient differentiated membrane electrode.

[0057] Example 4

[0058] Step 1: Pt on Vulacan XC-72 catalyst was placed in a bottle, and then IrO2 catalyst, 10 g of deionized water and a magnetic stirrer were added to obtain a dispersion solvent, and the dispersion solvent was stirred at a stirring speed of 600 rpm for 3 min;

[0059] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 10 minutes, and then add 10 g of ethanol to the mixed solution;

[0060] Step 3: Add platinum carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice water bath environment; disperse through a nano-scale sand mill, the speed of the disperser is 2000rpm, and the dispersion time is 30min; disperse the platinum carbon and iridium dioxide catalyst particles in the dispersion solvent, collect the dispersed catalyst slurry for degassing treatment, and then magnetically stir at 300rpm to form a colloidal solution;

[0061] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The blocks are then treated in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, so that the proton conductivity of the Nafion membrane is activated, and then placed in a blast drying oven at 60°C for 2 hours for standby use, to obtain a pretreated proton exchange membrane; then the catalyst slurry is coated on one side of the proton exchange membrane by a scraper coating method, and the distance between the scraper and the proton exchange membrane gradually increases along the vertical direction, so that the Pt / XC-72 catalyst and the IrO2 catalyst colloidal solution are coated on the anode side of the proton exchange membrane, and the colloidal solution thickness is differentiated in the vertical direction and the thickness increases linearly; finally, the proton exchange membrane is turned over, and the catalyst slurry is coated on the other side of the proton exchange membrane by a scraper coating method, and the distance between the scraper and the membrane is maintained along the vertical direction, so that the thickness of the catalyst colloidal solution of the proton exchange membrane is evenly coated in the vertical direction;

[0062] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalytic layers of the prepared proton exchange membrane, respectively, use PI film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 140°C, 7MPa pressure, and hot press for 2 minutes to obtain a gradient differentiated membrane electrode.

[0063] Example 5

[0064] Step 1: Pt on Vulacan XC-72 catalyst was placed in a bottle, and then IrO2 catalyst, 10 g of deionized water and a magnetic stirrer were added to obtain a dispersion solvent, and the dispersion solvent was stirred at a stirring speed of 600 rpm for 3 min;

[0065] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 10 minutes, and then add 10 g of ethanol to the mixed solution;

[0066] Step 3: Add platinum carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice water bath environment; disperse through a nano-scale sand mill, the speed of the disperser is 2000rpm, and the dispersion time is 30min; disperse the platinum carbon and iridium dioxide catalyst particles in the dispersion solvent, collect the dispersed catalyst slurry for degassing treatment, and then magnetically stir at 300rpm to form a colloidal solution;

[0067] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The pretreated proton exchange membrane is then placed in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, thereby activating the proton conductivity of the Nafion membrane. The pretreated proton exchange membrane is then placed in a blast drying oven at 60°C for 2 hours for standby use. The catalyst slurry is then coated on the anode side of the proton exchange membrane by a slit coating method, and the distance between the slit and the proton exchange membrane gradually increases along the vertical direction, thereby coating the Pt / XC-72 catalyst and the IrO2 catalyst dispersion on the anode side of the proton exchange membrane, achieving a gradient differentiation in the thickness of the anode side catalyst colloid solution in the vertical direction and a linear increase in thickness. The proton exchange membrane is turned over, and the catalyst slurry is coated on the other side of the proton exchange membrane by a slit coating method, and the distance between the scraper and the membrane is maintained along the vertical direction, so that the thickness of the cathode side catalyst colloid solution on the proton exchange membrane is uniformly coated in the vertical direction.

[0068] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalytic layers of the prepared proton exchange membrane, respectively, use PI film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 140°C, 7MPa pressure, and hot press for 2 minutes to obtain a gradient differentiated membrane electrode.

[0069] Example 6

[0070] Step 1: Place the Pt / C catalyst in a bottle, then add the IrO2 catalyst, 10 g of deionized water and a magnetic stirrer to obtain a dispersion solvent, and stir the dispersion solvent at a stirring speed of 600 rpm for 3 min;

[0071] Step 2: Mix the dispersion solvent with deionized water and Nafion solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 20 minutes, and then add 10 g of isopropanol to the mixed solution;

[0072] Step 3: Add platinum carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then continue ultrasonic cleaning in an ice water bath environment; quickly disperse through a crusher, and the dispersion time is 30 minutes; disperse the platinum carbon and iridium dioxide catalyst particles in the dispersion solvent, collect the dispersed catalyst slurry for degassing treatment, and then magnetically stir at 300rpm to form a colloidal solution;

[0073] Step 4: Cut the Nafion115 membrane into pieces with an area of ​​2×2cm 2The blocks are then treated in a 1L / mol sulfuric acid solution at 80°C for 30 minutes, and then rinsed with deionized water to remove surface and metal impurities, so that the proton conductivity of the Nafion membrane is activated, and then placed in a blast drying oven at 60°C for 2 hours for standby use to obtain a pretreated proton exchange membrane; the catalyst slurry is then coated on the anode side of the proton exchange membrane by screen printing, and the spraying thickness in the vertical direction gradually increases along the length of the proton exchange membrane, so that the Pt / C catalyst and IrO2 catalyst colloidal solution are coated on the anode side of the proton exchange membrane, and the thickness of the colloidal solution is differentiated in the vertical direction and the thickness increases linearly; the proton exchange membrane is turned over, and the catalyst slurry is coated on the cathode side of the proton exchange membrane by a slit coating method, and the distance between the scraper and the proton exchange membrane is maintained in the vertical direction to achieve uniform coating of the catalyst colloidal solution thickness in the vertical direction;

[0074] Step 5: Add corresponding anode and cathode gas diffusion layers on both sides of the anode and cathode catalytic layers of the prepared proton exchange membrane, respectively, use PET film frame for hot pressing and plastic sealing, put it in a metal pressing plate and put it into a hot press, set the hot plate temperature to 140°C, 10MPa pressure, and hot press for 1 minute to obtain a gradient differentiated membrane electrode.

[0075] The present invention also provides an application of the gradient-differentiated membrane electrode, wherein the membrane electrode is targeted at a specific "ammonia-hydrogen" fuel cell system application scenario.

[0076] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a gradient-differentiated membrane electrode, characterized in that: The steps include: Step 1: mixing a platinum-carbon catalyst, an iridium dioxide catalyst and deionized water to obtain a dispersion solvent; Step 2: Mix the dispersion solvent with deionized water and the perfluorosulfonic acid ionomer solution to obtain a mixed solution, place the obtained mixed solution in an ice water bath for ultrasonic cleaning for 20 to 35 minutes, and then add ethanol or isopropanol to the mixed solution; Step 3: Adding platinum-carbon catalyst or iridium dioxide catalyst to the mixed solution after ultrasonic cleaning again, and then ultrasonic cleaning again in an ice-water bath environment; so that the platinum-carbon and iridium dioxide catalyst particles are dispersed in the dispersion solvent to form a colloidal solution; Step 4: placing the proton exchange membrane on an ultrasonic spraying device for heating, spraying a colloidal solution containing a platinum-carbon catalyst and an iridium dioxide catalyst on the anode side and the cathode side of the proton exchange membrane respectively, wherein the thickness of the catalyst layer on the anode side of the proton exchange membrane gradually increases along the length direction of the proton exchange membrane; Step 5: subjecting the sprayed proton exchange membrane to hot pressing and plastic sealing treatment, placing gas diffusion electrodes on the cathode side and anode side of the proton exchange membrane after the plastic sealing treatment, and finally subjecting the proton exchange membrane to hot pressing treatment to obtain a gradient-differentiated membrane electrode.

2. The method for preparing a gradient-differentiated membrane electrode according to claim 1, characterized in that: In step 1, the dispersion solvent containing the platinum-carbon catalyst and the iridium dioxide catalyst also includes an organic solvent, and the organic solvent is any one or more of ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol or n-butanol.

3. The method for preparing a gradient-differentiated membrane electrode according to claim 1, characterized in that: In step 3, the mixed solution after ultrasonic cleaning is placed in an ultrasonic environment for ultrasonic crushing; A colloidal solution is formed; the mass ratio of the platinum-carbon catalyst, the iridium dioxide catalyst, the deionized water and the perfluorosulfonic acid ionomer solution in the dispersed solvent is (0.08-1.25): (0.02-0.15): (40-70): (15-30); during the ultrasonic crushing process, the frequency of the ultrasonic crushing is 10-44KHz, and the ultrasonic crushing time is 1-5h; the temperature range of the ice water bath is -8-3°C.

4. The method for preparing a gradient-differentiated membrane electrode according to claim 1, characterized in that: In step 4, before heating the proton exchange membrane, the proton exchange membrane is cut into a quadrilateral structure and immersed in deionized water, and the immersed proton exchange membrane is taken out from the deionized water and immersed in an acid solution, wherein the acid solution is sulfuric acid, phosphoric acid, hydrochloric acid or an organic acid, and the concentration range of the acid solution is 0.5 to 1.5 L / mol.

5. The method for preparing a gradient-differentiated membrane electrode according to claim 1, characterized in that: The colloidal solution containing the platinum-carbon catalyst and the iridium dioxide catalyst is sprayed on the anode side and the cathode side of the proton exchange membrane respectively by ultrasonic spraying, doctor blade coating, slit coating or screen printing.

6. The method for preparing a gradient-differentiated membrane electrode according to claim 5, characterized in that: When ultrasonic spraying is used for spraying, the spraying speed of the nozzle in the horizontal direction of the ultrasonic spraying equipment gradually increases along the vertical direction; when scraper coating is used for spraying, the distance between the scraper and the proton exchange membrane gradually increases along the vertical direction; when slit coating is used for spraying, the distance between the slit and the proton exchange membrane gradually increases along the vertical direction.

7. A gradient-differentiated membrane electrode prepared by the gradient-differentiated membrane electrode preparation method according to any one of claims 1 to 6, comprising an anode catalyst layer, a cathode catalyst layer, a proton exchange membrane, a cathode gas diffusion layer and an anode gas diffusion layer; the anode catalyst layer and the cathode catalyst layer are respectively covered on both sides of the proton exchange membrane, the cathode gas diffusion layer is covered on the anode catalyst layer, and the anode gas diffusion layer is covered on the cathode catalyst layer, characterized in that: The thickness of the anode catalyst layer gradually increases along the length direction of the proton exchange membrane. Both the anode catalyst layer and the cathode catalyst layer contain platinum metal, iridium metal element and perfluorosulfonic acid ionomer.

8. The gradient-differentiated membrane electrode according to claim 7, characterized in that: The anode catalyst layer and the cathode catalyst layer both include a platinum-carbon catalyst and a platinum alloy catalyst, wherein the alloying elements in the platinum alloy catalyst are one or more of Co, Ni, Ru, Cu, and Fe; the mass fraction of platinum in the platinum-carbon catalyst is 10 to 80%; the mass fraction of iridium metal elements in the anode catalyst layer and the cathode catalyst layer are both 50 to 90%; and the mass fraction of perfluorosulfonic acid ionomer in the anode catalyst layer is 20 to 35%.

9. The gradient-differentiated membrane electrode according to claim 7, characterized in that: The amount of platinum metal carrier on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane; the amount of iridium loaded on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane, the pore diameter on the anode catalyst layer gradually increases along the length direction of the proton exchange membrane, and the thickness of the anode catalyst layer increases linearly along the length direction of the proton exchange membrane; the thickness range of the anode catalyst layer is 5 to 15 um.

10. An application of the gradient-differentiated membrane electrode according to any one of claims 8 to 9, characterized in that: Used in the fuel cell field.

Citation Information

Patent Citations

  • Membrane electrode containing gradient cathode catalyst layer and preparation method and application thereof

    CN115133043A